Media Promosi Bisnis Potensi Wisata Daerah Bandung Dengan Aplikasi Virtual Reality - Triani, Ananda Risya; Adriyanto, Andreas Rio; Faedhurrahman, Deny (LPPM STMIK STIKOM Indonesia, 2018)
One of the industrial sectors that can increase foreign exchange in Indonesia is the tourism industry. In 2019, the tourism industry in Indonesia is projected to be the largest foreign exchange earner through oil and gas, coal and palm oil. One aspect that supports the development of industry is the readiness of ICT. Bandung is one of the cities in West Java, which has sought to develop ICT, but needs to be improved further from the central / regional government, to the executant of the tourism industry. Bandung has a tourism potential that consists of natural attractions, culture, shopping, and culinary interesting to explore both by domestic tourists and foreign tourists. Thus, information technology that contains relevant and interesting information by using the right business model. Research methodology in data list technique which is measurement, interview, and literature study. Mobile apps are one of the information technology tools used by todays society, therefore interactive and can be used via mobile devices. Creative concepts applied to the 360ââÂ° Virtual reality Panorama app. Through Virtual reality Panorama will create a different visual location, which can attract potential tourists to visit Bandung city destinations directly. In addition, the appropriate business model will be used on the system as part of the activity. It is expected that this research can support previous research in the field of visual communication design, ICT, and management.